2013
DOI: 10.1051/0004-6361/201322380
|View full text |Cite
|
Sign up to set email alerts
|

Manganese abundances in Galactic bulge red giants

Abstract: Context. Manganese is mainly produced in type II SNe during explosive silicon burning, in incomplete Si-burning regions, and depends on several nucleosynthesis environment conditions, such as mass cut between the matter ejected and falling back onto the remnant, electron and neutron excesses, mixing fallback, and explosion energy. Manganese is also produced in type Ia SNe. Aims. The aim of this work is the study of abundances of the iron-peak element Mn in 56 bulge giants, among which 13 are red clump stars. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 55 publications
(122 reference statements)
13
73
1
Order By: Relevance
“…Thus, from [Fe/H] ∼ −1, [Mn/Fe] begins to show an increasing trend toward higher metallicity, which is caused by the delayed enrichment of SNe Ia (Kobayashi & Nakasato 2011). Furthermore, this trend varies within the different Galactic components (Adibekyan et al 2012;Barbuy et al 2013), from cluster to field stars (Gratton 1989), and it is different for the Milky Way and dwarf galaxies (Prochaska & McWilliam 2000;North et al 2012). Measuring accurate abundances of Mn is thus also important for studying the structure of our Galaxy because, for example, there is observational evidence of the existence of low The authors explain this difference with the fact that Mn is produced at a higher fraction than Fe during SNIa, meaning that at a given metallicity, α-poor stars (which have been polluted by more SNIa) will have higher [Mn/Fe] ratios than their α-rich counterparts.…”
Section: Manganesementioning
confidence: 99%
“…Thus, from [Fe/H] ∼ −1, [Mn/Fe] begins to show an increasing trend toward higher metallicity, which is caused by the delayed enrichment of SNe Ia (Kobayashi & Nakasato 2011). Furthermore, this trend varies within the different Galactic components (Adibekyan et al 2012;Barbuy et al 2013), from cluster to field stars (Gratton 1989), and it is different for the Milky Way and dwarf galaxies (Prochaska & McWilliam 2000;North et al 2012). Measuring accurate abundances of Mn is thus also important for studying the structure of our Galaxy because, for example, there is observational evidence of the existence of low The authors explain this difference with the fact that Mn is produced at a higher fraction than Fe during SNIa, meaning that at a given metallicity, α-poor stars (which have been polluted by more SNIa) will have higher [Mn/Fe] ratios than their α-rich counterparts.…”
Section: Manganesementioning
confidence: 99%
“…An additional 13 field red clump stars were analysed by Hill et al (2011) based on both the UVES and the GIRAFFE spectra. We adopted the stellar parameters derived from the UVES spectra, which were not given in Hill et al (2011) but already reported in Barbuy et al (2013).…”
Section: Calculations Of C N and O Abundancesmentioning
confidence: 99%
“…We have adopted uncertainties in the atmospheric parameters of ±150 K for effective temperature, ±0.20 for surface gravity, ±0.10 in [Fe/H] and ±0.10 km s −1 for microturbulent velocity, as explained in Barbuy et al (2013).…”
Section: Uncertaintiesmentioning
confidence: 99%
“…Another 13 field red clump stars were analysed by Hill et al (2011) based on both the UVES and the GIRAFFE spectra. We adopted the parameters derived from the UVES spectra, which were not given in Hill et al (2011) but already reported in Barbuy et al (2013).…”
Section: Abundance Analysismentioning
confidence: 99%
“…We have adopted uncertainties in the atmospheric parameters of ±150 K for effective temperature, ±0.20 for surface gravity, and ±0.10 in [Fe/H] and ±0.10 km s −1 for microturbulent velocity, as explained in Barbuy et al (2013). The errors in [Zn/Fe] are computed by using model atmospheres with parameters changed by these uncertainties, applied to the stars B6-f1 and BW-f8.…”
Section: Errorsmentioning
confidence: 99%